Formation of ultracold singlet ground state 39K87Rb molecules via Feshbach-optimized photoassociation. (7th December 2022) - Yu, Zong-Han; Si, Bo-Wen; Sun, Zhi-Xin; Lyu, Bing-Kuan; Cong, Shu-Lin
Abstract: We investigate theoretically the formation of ultracold 39 K 87 Rb molecules on the lowest vibrational level of singlet ground electronic X 1 Σ + state via the Feshbach-optimized photoassociation. The probability density of colliding atomic pair at the short-range interatomic separation is significantly enhanced near Feshbach resonances. Due to the limitation of transition selection rule, the direct transition between singlet and triplet electronic states is forbidden. The electronic spin–orbit couplings between excited electronic states are used to transfer the population from the triplet electronic state to the singlet electronic state. By using the magnetic field and four laser pulses, the colliding 39 K and 87 Rb atoms near a magnetically induced Feshbach resonance are converted into the 39 K 87 Rb molecule. The final population on the lowest vibrational level of the X 1 Σ + state reaches 0.02126.